Detox Fashion Waste Water Treatment (Textile Science and Clothing Technology,, 2018)
This third volume on detox fashion highlights sustainable wastewater treatment methods, as well as techniques used by and the adoption of detox strategies by different brands in the textile sector. These aspects are addressed in three central chapters: Sustainable Wastewater Treatment Technologies; Review of the Utilization of Plant-based Natural Coagulants as Alternatives to Textile Wastewater Treatment; and New Waste Management through Collaborative Business Models for Sustainable Innovation.